PEMBENTUKAN KARAKTER INSAN KAMIL MELALUI PENGEMBANGAN SOFTSKILL DI UNIVERSITAS MUHAMMADIYAH JEMBER - Putra, Dhian Wahana (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
There is a specific relation between Islamic Education and Insan Kamil. A system and education are laid out well will be able to give birth to quality human spiritual or temporal essence of a man. This study aimed to see how soft skills can shape the character of students. The method used in this research is qualitative. The results showed that the development of soft skills in Muhammadiyah University of Jember there are five (5) types of development activities, namely (1) the group reasoning and science, (2) a group of talents, interests and abilities, (3) groups of well-being, (4) a group of social concern, (5) group support activities ?. In carrying out these activities Muhammadiyah University of Jember adopts an integrated curriculum, which combines the basic curriculum of higher education with a curriculum of AlIslam and Kemuhammadiyahan. The purpose of the implementation of the activities are integrated with kuriukulum Al-Islam and Kemuhammadiyahan is to maximize the academic potential, non academic, and spiritual students, so there is a balance between hard skills and soft skills are imbued with the spirit of the values that embodied human character plenary, in other terms referred to as a perfect man.. Keywords: Character, Insan Kamil, Softskill